Paradigma Pembelajaran Sejarah Abad Ke-21 dengan kompetensi 4C - Caraka Yoga Aprilya; Sumiyati; D Djono (LPPM Press, 2026)
History education in the twenty-first century is expected to move beyond the transmission of factual knowledge and chronological events toward the development of higher-order thinking skills relevant to contemporary educational demands. However, history instruction in many schools remains predominantly teacher-centered, limiting students' opportunities to develop twenty-first-century competencies and historical thinking skills in an integrated manner. This study aims to formulate a conceptual paradigm for twenty-first-century history education by integrating the 4C competencies (critical thinking, creativity, communication, and collaboration) with the principles of historical thinking. The study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Data were collected from seven academic databases—Google Scholar, Scopus, ERIC, DOAJ, Garuda, SINTA, and Crossref—covering publications from 2013 to 2026. After a rigorous screening process, 28 eligible studies were selected and analyzed using thematic analysis. The findings reveal that integrating the 4C competencies with historical thinking provides a comprehensive conceptual framework for history learning. Critical thinking is fostered through source analysis and evidence evaluation; creativity through evidence-based historical interpretation and representation; communication through the construction of historical arguments; and collaboration through inquiry-based and multiperspective learning activities. The study proposes the 4C-HT conceptual model, which positions the 4C competencies as disciplinary skills operationalized through authentic historical inquiry rather than as generic twenty-first-century skills. This model contributes to the development of more active, reflective, evidence-based, and student-centered history learning while strengthening historical literacy, civic awareness, and the competencies required in the twenty-first century.